Influences of Zinc Chloride on Fast Pyrolysis of Pinewood - Garrido-Lazo, R (Institute of Physics, 2022)
Fast pyrolysis is a thermochemical process which converts biomass into intermediate bio-oil and biochar products, which can be further processed to produce end products. Bio-oil is an organic liquid containing myriads of organic chemicals derived from the decomposition of cellulose, hemicellulose, and lignin components in lignocellulosic biomass. There are chemicals in bio-oil which are highly valuable as specialty chemicals, such as furfural, levoglucosan and levoglucosenone. Unfortunately, the amounts of these chemicals are typically too small, which makes it uneconomical to extract them from bio-oil. This work is focused on fast pyrolysis of pinewood, a well-known softwood used in paper industry. In this work, it was demonstrated that bio-oil containing higher fractions of furfural and levoguclosenone can be produced by treating pinewood feedstock with zinc chloride prior to pyrolysis. The batch pyrolysis studies by using a micropyrolyzer, a batch tubular reactor, and a thermogravimetric analyzer showed that the amounts of zinc chloride impregnated to pinewood feedstock significantly affect the yields of bio-oil and biochar products and the composition of chemicals in bio-oil. Increasing the concentration of zinc chloride solution used for pretreating the feedstock resulted in higher yields of biochar containing higher amount of the salt. Optimum concentrations of furfural and the two sugars in bio-oil product seemed to be obtained from pyrolysis of pinewood that was pretreated with 5wt% zinc chloride solution. Pretreatment with higher salt concentration reduced the concentration of levoglucosan but did not affect the other two valuable chemicals. © Published under licence by IOP Publishing Ltd.